Application of a limit Function Of Negative Hyper-geometric Distribution in Option Pricing. (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
This work introduces limit function of a negative hyper geometric distribution of the form .where  and, which is applied in option pricing using wealth equation and some martingale tools. This paper present a simple discrete time model in compares. This work conclude that limit of negative hyper geometric as  can be associated with financial terms that can be used to evaluate option values (non dividend)  which gives the same numerical with CRR model.